Histórias sem fim: uma abordagem complexa sobre universos cinematográficos - Ferreira, Antonio Davi Delfino (2024)
This research aims to present conceptual and methodological discussions about cinematic universes from a complex approach. Integrating different films, film series, and entertainment franchises, cinematic universes are expressions specific of contemporary commercial cinema, remixing structures of narrative continuity and commercial strategies of the film industry historically tested in a particular context of sophistication of relations between languages in media convergence. We consider cinematic universes as contemporary and commercial translations of the act of narrating, present in our various cultures since we understand ourselves as members of social organizations, in which the power of the encounter and the reunion of forces builds the recognition of common worlds. This power is transformed into consumer appeal in a collector's cinema, marked by the resignification of the cinematic experience as an access point to some of the many chapters of continuous stories that extend into transmedia franchises. For this reason, we adopt an investigative stance that considers both diegetic and extradiegetic elements to investigate cinematic universes as living things (Ingold, 2012), dynamic phenomena that operate in sociocultural, narrative, and artistic practices simultaneously. This stance results in a theoretical construct based mainly on complex thinking (Morin, 2005), dialogism (Bakhtin, 2008), and transtextuality (Genette, 1989) under a critical prism that leads to the proposition of a decentralized approach to scientific production on these cinematic universes in popular culture.